Rejuvenating bone marrow hematopoietic reserve prevents regeneration failure and hepatic decompensation in animal model of cirrhosis - Nautiyal, Nidhi; Maheshwari, Deepanshu; Kumar, Dhananjay; Rao, E. Pranshu; Tripathi, Dinesh Mani; Kumar, Sandeep; Diwakar, Sunidhi; Bhardwaj, Manisha; Mohanty, Sujata; Baligar, Prakash; Kumari, Anupama; Bihari, Chhagan; et al. (Frontiers in Immunology, 2024)
Background and Aim: Bone marrow stem cells (BM-SCs) and their progeny play a central role in tissue repair and regeneration. In patients with chronic liver failure, bone marrow (BM) reserve is severally compromised and they showed marked defects in the resolution of injury and infection, leading to liver failure and the onset of decompensation. Whether BM failure is the cause or consequence of liver failure during cirrhosis is not known. In this study, we aimed to determine the underlying relationship between BM failure and regeneration failure in cirrhosis.Methodology: C57Bl/6(J) mice were used to develop chronic liver injury through intra-peritoneal administration of carbon tetrachloride (CCl4) for 15 weeks (0.1-0.5 ml/kg). Animals were sacrificed to study the transition of cirrhosis and BM defects. To restore the BM-SC reserve; healthy BM cells were infused via intra-BM infusion and assessed for changes in liver injury, regeneration, and BM-SC reserve.Results: Using a CCl4-induced animal -model of cirrhosis, we showed the loss of BM-SCs reserve occurred before regeneration failure and the onset of non-acute decompensation. Intra-BM infusion of healthy BM cells induced the repopulation of native hematopoietic stem cells (HSCs) in cirrhotic BM. Restoring BM-HSCs reserve augments liver macrophage-mediated clearance of infection and inflammation dampens neutrophil-mediated inflammation, accelerates fibrosis regression, enhances hepatocyte proliferation, and delays the onset of non-acute decompensation.These findings suggest that loss of BM-HSCs reserve underlies the compromised innate immune function of the liver, drives regeneration failure, and the onset of non-acute decompensation.We further provide the proof-of-concept that rejuvenating BM-HSC reserve can serve as a potential therapeutic approach for preventing regeneration failure and transition to decompensated cirrhosis.